Peningkatan Kapasitas Manajemen Keuangan UMKM Melalui Pelatihan Dan Pendampingan Perhitungan Titik Impas Pada Usaha Maco Adaik Di Kabupaten Tanah Datar - Prima Fithri; Silmi Silmi; Hanalde Andre (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy, yet many traditional businesses lack adequate financial literacy, particularly regarding the calculation of the Break Even Point (BEP), which is essential for determining the breakeven level and profit planning. This community service program aims to improve BEP understanding among MSME actors of Maco Adaik in Nagari Sungayang. The program was implemented from July to September 2025 at the Sungayang Village Hall using a participatory approach through interactive lectures, simulations, and group discussions based on real business data. Evaluation was conducted using pre-test and post-test with Likert-scale questionnaires to measure participants’ comprehension. The training results showed a significant improvement, with 70% of participants able to calculate BEP independently after the program. Analysis of Maco Adaik business data indicated that breakeven is achieved at 30 packages per month with a selling price of IDR 18,100, fixed costs of IDR 300,000, and variable costs of IDR 8,083 per unit. This understanding encouraged participants to develop more structured pricing and production strategies and raised awareness of cost recording. Social impact was evident through active community involvement and strengthened entrepreneurial capacity based on local potential. This program effectively enhanced MSME financial literacy and is expected to contribute to business sustainability. For further development, digital-based financial recording training and collaboration with BUMNag are recommended to strengthen business institutions and replicate the program in other villages.